MAGNESIUM SULPHATE VERSUS LIGNOCAINE AT INDUCTION FOR HEMODYNAMIC RESPONSE IN PATIENTS UNDERGOING CARDIAC SURGERY - Khalid, Valia; Khuwaja, Muhammad Amin; Ahmed, Aftab; Kumar, Kamal; Iqtdar, Rabia; Hussain, Syed Aqeel (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the hemodynamic stability during laryngoscopy with magnesium sulphate versus lignocaine in patients undergoing cardiac surgery at a tertiary cardiac centre. Study Design: Prospective observational study. Place and Duration of Study: Adult Cardiac Surgery department, National Institute of Cardiovascular Diseases, Karachi Pakistan, from Jan and Apr 2021. Methodology: This study evaluated 100 patients ASA II, III & IV, aged 18-65 years that were planned for cardiac surgeries after performing intubation procedure under general anesthesia. The patients had been divided into groups of two: group A received dose of 1.5 mg.kg-1 of lignocaine and group B, dose of 50 mg.kg-1 of drug magnesium sulphate, before anesthetic induction. Heart rate and blood pressure are two parameters that had been measured in two groups before intubation and 5 minutes after intubation after delivering both study drugs. Results: In both groups there was an increase in HR and BP at laryngoscopy and intubation. Among patients receiving Magnesium sulphate and lidocaine, both groups showed good efficacy and stability for hemodynamic management after laryngoscopy and intubation thus magnesium sulphate has proven to be a potential alternative. Conclusion: Doses of magnesium sulfate are quite enough to attenuate the response of hemodynamics to intubation of trachea, with results parallel to drug lidocaine.